AVALIAÇÃO DA QUALIDADE DA ÁGUA PARA ADEQUAÇÃO DE SISTEMAS DE TRATAMENTO DE ÁGUA NA AMAZÔNIA - Damaceno, Viviane Maia (2012)
Riparian communities in the Amazonia suffer from a number of aquatic transmitted diseases, because they frequently consume water supplied directly by the river, with no treatment. Due to the fact that these communities area located in remote areas, adduction of water would be a challenging and expensive work, so a better solution would be the development of small water treatment plants in the neighborhood of the community. In order to carry out the choice of the technology a major issue is to determine the characteristics of the water that is going to supplied the system. For instance, if the waters are too acid, the addition of alluminium compounds to promote flocculation of particles, may, instead promote dissolution of the alluminium that is responsible for Alzheimer disease. Based on a large set of water quality data it was aimed to establish contour maps of temperature, pH, turbidity, conductivity, dissolved oxygen, flow rate and suspended matter concentration. The data were obtained from the Brazilian National Waters Agency that reports 54 water quality stations in the whole Amazonia region, with data since 1976 until 2005. The set of data for each parameter was organized in dry and wet seasons a and the average values for each season (z), together with geographic coordinates (x, y) was plotted in collored contours maps in the software Surfer. A total of 14 contour maps were constructed for each parameter and for wet and dry seasons. The results show that suspended matter concentration reach values of almost 1 g L-1 in both periods, with higher concentrations in Southwestern portion. Conductivity show the same pattern during dry season while in wet season, this parameter is more evenly distributed. The lowest pH values were observed in the Northwester portion, in the Basin of the Negro River, during both periods, while the Eastern portion of Amazonia presents values closer to neutrality. Dissolved oxygen is evenly distributed throughout the Amazonian environment, reaching values close to saturation. Flow rates are extremely high, mainly in the ower stretch of the Amazon River, reaching values above 140,000 m3 s-1. It is concluded that simple treatment plants should be developped for the Riparian populations, because maintenance should not imply very complicate procedures. The systems that remove particulate matter should be very performing, and in the Northwestern portion should not use alluminium based flocculants. Finaly, although very little coliform bacteria data is available, drinking water treatment should not use chloride in the desinfection step, 14 because in the presence of humic substances, the formation of trihalomethanes may be also harmful to populations.